2022
DOI: 10.3390/nu14122481
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin Bioavailability Is Increased by the Presence of 2S-Diastereoisomer and Micronization—A Randomized, Crossover and Double-Blind Clinical Trial

Abstract: Hesperidin is a flavanone abundantly found in citrus fruits for which health beneficial effects have been reported. However, hesperidin shows a low bioavailability among individuals. The aim of this study was to evaluate the effects of the micronization process and 2R- and 2S-hesperidin diastereoisomers ratio on hesperidin bioavailability. In a first phase, thirty healthy individuals consumed 500 mL of orange juice with 345 mg of hesperidin, and the levels of hesperidin metabolites excreted in urine were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Interestingly, polyphenols have prebiotic-like properties that enhance the relative abundance of beneficial bacteria, strengthening their antioxidant capability [ 72 , 73 ]. In addition, the metabolites of polyphenols in the colon segment catabolized by microbiota results in increased anti-inflammatory activity [ 74 , 75 ]. A great number of studies have shown that polyphenolic compounds positively regulate antioxidant signaling pathways, such as Nrf2 [ 76 , 77 ], to intensify the intestinal mucosal barrier, which is also beneficial for the homeostasis of the gut microbiota [ 78 , 79 , 80 ].…”
Section: Polyphenols Retard Oxidative Stress and Inflammation Via Mod...mentioning
confidence: 99%
“…Interestingly, polyphenols have prebiotic-like properties that enhance the relative abundance of beneficial bacteria, strengthening their antioxidant capability [ 72 , 73 ]. In addition, the metabolites of polyphenols in the colon segment catabolized by microbiota results in increased anti-inflammatory activity [ 74 , 75 ]. A great number of studies have shown that polyphenolic compounds positively regulate antioxidant signaling pathways, such as Nrf2 [ 76 , 77 ], to intensify the intestinal mucosal barrier, which is also beneficial for the homeostasis of the gut microbiota [ 78 , 79 , 80 ].…”
Section: Polyphenols Retard Oxidative Stress and Inflammation Via Mod...mentioning
confidence: 99%
“…Hesperidin has a chiral carbon in position 2, generating (R)- and (S)-enantiomers. The predominant form in nature is the 2S-diastereoisomer, with a ratio of 8/92 for 2R-/2S-hesperidin diastereoisomers in fresh orange juice [ 14 , 15 ]. Figure 2 presents the structure of hesperidin and its general metabolic scheme.…”
Section: Hesperidin: Chemical Properties Sources and Safety Profilementioning
confidence: 99%
“…Poor [157] 610.6 and 250-255 °C Improvement in plasma insulin levels and total blood lipid profiles [158].…”
Section: Abbreviationsmentioning
confidence: 99%